Analysis of Community Participation and Satisfaction with the Engku Putri Square as an Open Sports Space in Batam City - Dodok, Dodok; Handayani, Widya; Lestari, Hikmah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to investigate community participation and satisfaction with the Engku Putri Square as an open sports space in the city of Batam to find out how far the government has implemented the National Sports System Law (UU SKN) through the two dimensions of the Sports Development Index (SDI). Case studies were chosen as an approach to achieve the objectives of this research. Data were obtained through interviews, observations, and documents. The interviewees were 16 community members who used the Engku Putri square as a place to exercise. Observations were made on daily sports activities, the condition of the facilities, and the atmosphere at the Engku Putri square. Document data was obtained from the relevant SKPD, namely the Public Works Department (DPU) Parks section, the Indonesian Community Recreational Sports Federation (FORMI) in the city of Batam, and the Internet. Data analysis uses a thematic analysis approach by reading data, grouping initial codes, determining themes, and writing reports. The results are presented through a description of the environmental characteristics of Engku Putri Square, Batam City, tabulated results of community participation and satisfaction in several themes. Participation is the initial discussion through calculating the SDI participation index with intermediate criteria. Meanwhile, satisfaction is categorized into four major themes, namely (1) quality and service, (2) price, (3) emotional factors, and (4) convenience. Each of them was at a satisfactory level with several inputs as follows: (1) the need for additional sports facilities in the Engku Putri square, Batam city, (2) attention to the maintenance of facilities in the Engku Putri town square, Batam city, and (3) observing cleanliness in the Engku Putri square, Batam city.